Conceptual Exploration of the Appointment of Murshid in Tarekat Qadiriyah Naqsyabandiyah Suryalaya Islamic Boarding School with a Da'wah Communication Approach - Marzuqi, Muhammad Ganda; Nurdin, Ali (Studi Multidisipliner: Jurnal Kajian Keislaman, 2025)
One of the important roles in the Islamization process in the archipelago is the tariqat. Tarekat is literally a "path" referring to a system of meditation exercises or practices dhikr, wirid, etc. In this study, it focuses on da'wah communication in the tarekat, especially Mursyid or the teacher of the tarekat in communicating to the congregation or prospective students in the procession of bai'at of the Qadiriyah wa Naqsyabandiyah Tarekat. This research adopts a qualitative approach to describe the problems and focus of the research. The data collection method uses a descriptive method of analysis designed to obtain information. Data analysis in qualitative research is carried out during the data collection process. The data analysis techniques proposed by Miles and Hubermen include three activities, namely Data Reduction, Data Presentation, and Conclusion Drawn. In this Stimulus Organism Response communication model, the main focus is on the message conveyed as well as efforts to foster motivation in communicators, so that they can quickly receive messages and experience behavioral changes. Based on the understanding of the Stimulus Organism Response model, it can be concluded that this communication is very important to be applied by the Murshid of the Qadiriyah wa Naqsyabandiyah order in Rejoso Jombang, because it can have a positive impact on the students of the order and improve the quality of understanding of the students of the Qadiriyah wa Naqsyabandiyah order in Rejoso Jombang.